2009
DOI: 10.1371/journal.pone.0006755
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Hypofunction Leads to Generalized and Persistent Aberrant γ Oscillations Independent of Hyperlocomotion and the State of Consciousness

Abstract: BackgroundThe psychotomimetics ketamine and MK-801, non-competitive NMDA receptor (NMDAr) antagonists, induce cognitive impairment and aggravate schizophrenia symptoms. In conscious rats, they produce an abnormal behavior associated with a peculiar brain state characterized by increased synchronization in ongoing γ (30–80 Hz) oscillations in the frontoparietal (sensorimotor) electrocorticogram (ECoG). This study investigated whether NMDAr antagonists-induced aberrant γ oscillations are correlated with locomoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
223
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(269 citation statements)
references
References 72 publications
45
223
0
Order By: Relevance
“…This finding is also in accordance with previous results in cortical slices where NMDA blockers suppress the lower frequencies (53). At the same time, we found that NMDA-receptor blockers enhanced γ-oscillations, in accordance with previous results obtained with the systemic application of NMDA antagonists in rodents (78) and with local application in the visual cortex of monkeys (79).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is also in accordance with previous results in cortical slices where NMDA blockers suppress the lower frequencies (53). At the same time, we found that NMDA-receptor blockers enhanced γ-oscillations, in accordance with previous results obtained with the systemic application of NMDA antagonists in rodents (78) and with local application in the visual cortex of monkeys (79).…”
Section: Discussionsupporting
confidence: 93%
“…9 The emergence and recovery processes were characterized by increased high gamma activity and coherence. Similar increases in high gamma power and coherence have been reported after subanaesthetic doses of ketamine in rats [29][30][31] and humans. 32 In addition, subanaesthetic ketamine in rats induces hyperlocomotion, [29][30][31] which has been attributed to increases in power and coherence in higher gamma frequencies in the basal ganglia motor circuit.…”
Section: Discussionsupporting
confidence: 79%
“…The resulting hyperglutamatergic state is believed to mediate the enhanced field gamma activity by stimulating kainate and AMPA receptor-mediated activation of the cortical interneuron-pyramidal cell network (McNally et al, 2011;Roopun et al, 2008). Indeed, a robust increase in field gamma oscillations is one of the most consistent findings in response to systemic treatment with NMDA antagonists (Hakami et al, 2009;Kocsis, 2012;Sebban et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To understand whether the induced gamma is a mere reflection of the elevation in baseline gamma activity that NMDA antagonists are well known to engender (Hakami et al, 2009;Kocsis, 2012;Sebban et al, 2002), we compared induced power through duration of train stimulation with the total gamma band power at the beginning of each epoch when there was no auditory stimulation. We found a highly significant positive correlation (Pearson's r) and no statistical difference between the two measures (paired t-test; data not shown) under all treatment conditions, suggesting that induced power in our paradigm was merely reflecting the gamma power present in the signal.…”
Section: Induced Powermentioning
confidence: 99%